1994
DOI: 10.1002/jts.2490070404
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic responses among battered women who kill

Abstract: This study compared levels of violence, social support, and post-traumatic stress between battered women charged with a violent crime against an abusive partner and those seeking help from a mental health clinic. Results indicated that forensic battered women were more likely than clinical battered women to report experiencing severe violence, including sexual abuse, in their relationships. Women in the forensic sample also reported less social support and greater post-traumatic stress than women in the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Social support has been shown to be important for health and quality of life (Friedland, Renwick, & McColl, 1996;Gielen et al, 2001) and, based on this study's findings, greater social support appeared to protect against experiencing further violence. Previous research has shown that social support may be important in reducing the risk of experiencing violence by helping women end abusive relationships (Bowker, 1984;O'Campo et al, 2002;Ulrich, 1998) and conferring protection or serving as a buffer against ongoing abuse (Dutton et al, 1994). A recent study of women in university clinic settings indicates that social and emotional support may enhance psychological well-being among women who have experienced physical violence from their partners, and that informal support including expressions of caring and encouragement from family, friends, and clinicians is beneficial (Coker et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support has been shown to be important for health and quality of life (Friedland, Renwick, & McColl, 1996;Gielen et al, 2001) and, based on this study's findings, greater social support appeared to protect against experiencing further violence. Previous research has shown that social support may be important in reducing the risk of experiencing violence by helping women end abusive relationships (Bowker, 1984;O'Campo et al, 2002;Ulrich, 1998) and conferring protection or serving as a buffer against ongoing abuse (Dutton et al, 1994). A recent study of women in university clinic settings indicates that social and emotional support may enhance psychological well-being among women who have experienced physical violence from their partners, and that informal support including expressions of caring and encouragement from family, friends, and clinicians is beneficial (Coker et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although women in battering relationships do not routinely view the social support they receive with satisfaction (El-Bassel et al, 2000), in a study of 390 low-income women in Baltimore who experienced physical or sexual violence during adulthood, family and friends were identified as the typical source of help when attempting to leave a violent relationship (O'Campo et al, 2002). Beneficial social relationships may additionally reduce risk of victimization by conferring protection in a harsh environment (Dutton et al, 1994).…”
mentioning
confidence: 99%
“…2 The buffering effects of social support on stress in general, and on mental and physical health problems among abused women especially, have long been recognized in research (see Cohen & Wills, 1985;Coker et al, 2002). Applied to IPH, research by Dutton, Hohnecker, Halle, and Burghardt (1994) shows that women charged with attempted or actual homicide of their abusive partner experienced less perceived social support prior to the homicide than a control sample of abused women seeking mental health treatment.…”
Section: Factors Conditioning the Effect Of Strain On Intimate Partnementioning
confidence: 99%
“…Women's forgetfulness was framed using clinical terms such as posttraumatic stress disorder, denial, and repression (e.g., M. A. Dutton, Hohnecker, Halle, & Burghardt, 1994;Harvey & Martin, 1995), explaining those phenomena as serving a protective function for the "victim." Regarding men, on the other hand, the denial or minimization of violence has been explained as the need to detract from the consequences of the violent act and as attempts to construct a positive and normative self-image (e.g., Helfritz et al, 2006;Holtzworth-Munroe & Hutchinson, 1993;Miller, 1995).…”
Section: Disremembering Violence: Denial Minimization and Attributimentioning
confidence: 99%